Introuvables Assidéens - Nodet, Étienne (Revue biblique, 2024)
The 'Hasideans' of the Maccabean books never had any existence as a group: the Greek word is a transcription of the Hebrew, coined by the translator, who created a Greek entity devoid of any connection with the Pharisees or Essenes.